Characteristics of infantile convulsions and choreoathetosis syndrome caused by PRRT2 mutation - Yaxian Deng; Juanyu Xu; Chunmei Yao; Lei Wang; Xiaohuan Dong; Chengsong Zhao (Wiley, 2022)
ABSTRACT Importance Infantile convulsions and choreoathetosis (ICCA) is a rare neurological disorder. Many affected patients are either misdiagnosed or prescribed multiple antiepileptic drugs. Objective To explore therapeutic drug treatments and dosages for ICCA in children. Methods Detailed clinical features (e.g., past medical history and family history), genetic features, and treatment outcomes were collected from the records of six patients with ICCA. Results Mean age at paroxysmal kinesigenic dyskinesia (PKD) onset was 8 years 8 months (range, 3-12 years); the clinical presentation was characterized by daily short paroxysmal episodes of dystonia/dyskinesia. All patients had infantile convulsions at less than 1 year of age, and the mean onset age was 5.5 months (range, 4-7 months). Two patients had a family history of ICCA, PKD, or benign familial infantile epilepsy. Whole exome sequencing identified the c.649-650insC mutation in PRRT2 in six patients; three mutations were inherited and three were de novo. All patients were prescribed low‐dose carbamazepine and showed dramatic improvement with the complete disappearance of dyskinetic episodes after 3 days. They attended follow‐up for 5-17 months and were attack‐free until the final follow‐up. Interpretation PRRT2 mutations are the primary cause of ICCA. Low‐dose carbamazepine monotherapy is effective and well‐tolerated in children.